Evaluating the basic elements of transparency of regional fisheries management organizations. (July 2015) - Clark, Nichola A.; Ardron, Jeff A.; Pendleton, Linwood H.
Abstract: This paper reports on the first global study of regional fisheries management organization (RFMO) transparency. It was prompted by recent scholarship that suggests that RFMOs are failing to meet their conservation and management mandates and that transparency is a critical element of this performance. In this study, 11 RFMOs were evaluated using 34 questions, divided into three sections: (i) access to full, up-to-date and accurate information; (ii) public participation in decision-making; and (iii) access to outcomes. Secretariats for all 11 RFMOs were contacted, and all responded, to correct and comment on initial findings and to share additional information. The total scores in this study reflect transparency as measured against current good practices in RFMOs as a whole, rather than some sort of idealistic benchmark. Each question should therefore be seen as a diagnostic tool that shows where some RFMO(s) fall short and how they can correct the shortfall based on the practices of their peers. These results have highlighted a number of good practices amongst RFMOs, with no single RFMO standing out as having particularly poor transparency practices. On the other hand, there also were not any RFMOs that had exemplary transparency practices in every respect and all RFMOs still have room to improve upon their basic transparency practices. This first transparency assessment is necessarily broad in nature and considers only very basic elements of transparency. It is to be expected that as RFMO practices become more sophisticated, so will the techniques and criteria of future transparency assessments.